Main street revisited : time, space, and image building in small-town America - Francaviglia, Richard V. (American land and life series., 1996)
Main Street has come to symbolize a place of honest aspirations and few pretenses, a place where economics, community pride, and entertainment generate an intuitive appreciation of the small town as a vital part of the American experience. As an archetype for an entire class of places, Main Street has become one of America's most popular and idealized images. In Main Street Revisited, the first book to place the design of small downtowns in spatial and chronological context, Richard Francaviglia finds the sources of romanticized images of this archetype, including Walt Disney's Main Street USA, in towns as diverse as Marceline, Missouri, and Fort Collins, Colorado. Francaviglia interprets Main Street both as a real place and as an expression of collective assumptions, designs, and myths; his Main Streets are treasure troves of historic patterns. Using many historical and contemporary photographs and maps from his extensive fieldwork and research, he reveals a rich regional pattern of small-town development that serves as the basis for American community design. He underscores the significance of time in the development of Main Street's distinctive personality, focuses on the importance of space in the creation of place, and concentrates on popular images that have enshrined Main Street in the collective American consciousness. As a historical geographer with a long-standing interest in American popular culture, Francaviglia looks sympathetically but realistically at the ways in which Main Street's image developed and persists. He reaffirms that life can imitate art, that the cherished icons surrounding Main Street have become the substance of popular culture. Ultimately, his book is about the material culture that architects, town developers, and image makers have left us as their legacy. Seen through the lives of the visionaries who created them in their search for the perfect community, Main Streets above all symbolize both individual and collective human energy and dreams.